Body movement as a digital biomarker in chronic pain rehabilitation: a real-world pilot study using virtual reality - Liikkanen, Sammeli; Jalkanen, Tero; Mäkinen, Mika; Huttunen, Teppo; Kilpeläinen, Reijo; Reijula, Jori; Heimonen, Jonna; Mäkiniemi, Anssi; Gentile, Giovanni; Eccleston, Christopher (Frontiers in Virtual Reality, 2025)
IntroductionChronic pain (CP) is a major public health problem. Reliable measurement of movement, activity, and other changes due to chronic pain and its treatment is a challenge in healthcare. Wearable data collected from randomized clinical trials contains potential signals that could be further developed into digital biomarkers.MethodsIn a community clinic setting patients suffering from musculoskeletal disorders with chronic pain used a novel digital therapeutic intervention using virtual reality (Rohkea™ VR Therapy). Movement and clinical assessment data were collected using the sensors in the Oculus Quest. Wearable data were collected during the study interventions (frequent treatment sessions of Rohkea™ VR Therapy). Data were analyzed using exploratory statistical analysis.ResultsIn line with the earlier research, participants with chronic pain were able to increase the movement speed of the hand controllers during the intervention. They were also more cautious in moving their head compared to a reference group. Participants were less likely to reach out with their active hand than the reference group. Additionally, those with chronic pain had more difficulties with exercises in which they were required to pick up virtual objects situated lower in the virtual reality environment. Participants were able to increase their range of motion during the intervention. Given the small sample size, the results should be viewed as tentative and supportive of earlier findings from randomized controlled trials.Discussion/ConclusionThe findings reinforce previous results observed in the randomized controlled trials. That similar findings occur in both a clinical trial and a real-world environment is encouraging and is further support for implementation of a virtual reality intervention in everyday clinical settings.